Multi planes balancing of rotating element / Muhammad Zuraidi Mohd Shukri - Mohd Shukri, Muhammad Zuraidi (2009)
Unbalance is the most common source of vibration in machines with rotating parts. Unbalance in rotor is the result of an uneven distribution of mass causes the rotor to vibrate excessively at running speed .Balancing in rotors prevent excessive loading of bearings and avoid fatigue failure, thus increasing the useful of machinery. In this project, multiple planes unbalance problem was used to induce dynamic unbalance problem and theoretical calculation using influence coefficient method was use to solve it. The vibratory analysis of rotating machine was used to illustrate this behavior. This experimental procedure was carried out using trial mass calculation the influent coefficient and then the corrected mass value and location was experimentally carried out. Finally, the balanced rotor is trimmed with additional mass to perfectly balance the rotor. Based on the result of mass balance, it is expected that the theoretical result and experiment result will be identical.